2017
DOI: 10.1093/mnras/stx473
|View full text |Cite
|
Sign up to set email alerts
|

Active galactic nuclei feedback, quiescence and circumgalactic medium metal enrichment in early-type galaxies

Abstract: We present three-dimensional hydrodynamical simulations showing the effect of kinetic and radiative AGN feedback on a model galaxy representing a massive quiescent low-redshift early-type galaxy of M * = 8.41 × 10 10 M , harbouring a M BH = 4 × 10 8 M black hole surrounded by a cooling gaseous halo. We show that, for a total baryon fraction of ∼ 20% of the cosmological value, feedback from the AGN can keep the galaxy quiescent for about 4.35 Gyr and with properties consistent with black hole mass and X-ray lum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 143 publications
(206 reference statements)
2
53
0
Order By: Relevance
“…Despite adopting various numerical methods, simulations of AGN feedback and cooling flow problem often reveal formation of a massive long-lived cold disk in the vicinity of the central SMBH (e.g., Li & Bryan 2014a;Eisenreich et al 2017;Qiu et al 2018;Wang et al 2019). However, the observed molecular gas rarely appears to be rotationally supported in either elliptical galaxies (Young et al 2011) or central cluster galaxies (Russell et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite adopting various numerical methods, simulations of AGN feedback and cooling flow problem often reveal formation of a massive long-lived cold disk in the vicinity of the central SMBH (e.g., Li & Bryan 2014a;Eisenreich et al 2017;Qiu et al 2018;Wang et al 2019). However, the observed molecular gas rarely appears to be rotationally supported in either elliptical galaxies (Young et al 2011) or central cluster galaxies (Russell et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They can reproduce the observational results and compare the X-ray properties in detail [5][6][7][8]. References [5,6] applied 2D high-resolution hydro simulations and considered stellar feedback, dynamical (rotation), and structural (flattening) parameters as well as AGN feedback, and References [7,8] applied 3D cosmological simulations. While the differences among different simulations and different parameters/recipes are to yet be understood, in general they can reproduce the observed relations among L X,GAS , T GAS , M TOTAL (or M within 5 Re).…”
Section: Comparison With Simulationsmentioning
confidence: 97%
“…Recent numerical simulation studies [5][6][7][8] have further attempted to reproduce the observed scaling relations, in order to constrain the physical mechanisms that shape the hot ISM.…”
Section: X-ray Scaling Relationsmentioning
confidence: 99%
“…Still, more and more observations confirm the existence of wind in both LLAGNs (Cheung et al 2016;Crenshaw & Kraemer 2012;Tombesi et al 2014) and the hard state of black hole Xray binaries (Homan et al 2016), where a hot accretion flow is believed to operate. In many works, winds have been included although without explicitly emphasizing the mode of feedback (e.g., Ostriker et al 2010;Ciotti, Ostriker & Proga 2010;Eisenreich et al 2017). Achieving a sufficiently rapid reddening of moderately massive galaxies without expelling too many baryons has been challenging for simulations of galaxy formation.…”
Section: Introductionmentioning
confidence: 99%
“…the radiative heating. This feedback mechanism is ignored sometimes in previous works (but see e.g., Ciotti & Ostriker 2001;Ostriker et al 2010;Choi et al 2012;Gan et al 2014;Eisenreich et al 2017), perhaps because it is thought that the radiation of hot accretion flow is too weak. However, based on the following reasons, it is necessary to study its potential role in feedback.…”
Section: Introductionmentioning
confidence: 99%